Development of poly (methyl methacrylate-co-methacrylic acid) based electrolytes with synthesized and commercial ionic liquids for dye sensitized solar cells / Vhaissnavi Sundararajan - Vhaissnavi , Sundararajan (2021)
A persistent challenge for expanding global population and soaring economic progress has always been ensuring everyone has enough access to energy supply. At present, the high dependency on fossil fuel derived energy has led to a crisis that necessitated a shift of attention towards greener energy sources like solar. Solar energy serves as the most consistent back up energy and the best option for environmental conservation. Among the listed solar harvesters, dye sensitized solar cells (DSSCs) bring about vast potential in efficient conversion of solar to electrical energy. The fact that this discovery has not reached its pinnacle and every constituent of the cell still needs working on, a popular research interest would be the replacement of liquid electrolytes with gel polymer counterparts. Being a hybrid, gel polymer electrolytes (GPEs) retain the cohesive nature of solid electrolytes and stay diffusive as liquid electrolytes producing reasonable ionic conductivity and maintains good contact between components within the DSSCs., In that perspective, this work examines a series of poly(methyl methacrylate-co-methacrylic acid) P(MMA-co-MAA) based PE system for DSSCs. Initial sample preparation steps were modified by varying the ratio of I2/I3ˉ redox mediator from a sodium salt, copolymer and solvent used. As a part of secondary electrolyte systems studied, novel quinolinium based ionic liquids (ILs) were incorporated to the best single salt system. Great care was taken during the synthesis and purification of N-butyl-6-methylquinolinium bis(trifluoromethylsulfonyl) imide [C4mquin][NTf2] and N-butyl-6-methylquinolinium iodide [C4mquin][I] ILs in order to achieve low impurity levels. Exploring the new cation-anion combined IL for the purpose of DSSCs was necessary to achieve better and more sustained electrolyte conductivity. Subsequently, the prepared electrolyte mixtures were tested with a standard DSSC configuration of glass/FTO/TiO2/N719 dye/electrolyte/Pt/FTO/glass with active area of 0.3 cm2. The single salt system samples were able to achieve highest ionic conductivity and power conversion efficiency (PCE) of 1.07 mS cm-1 and 2.34%, respectively. Remarkably, upon the addition of the quinolinium IL, the ionic conductivity and PCE had increased to 2.26 mS cm-1 and 5.67%, respectively for [C4mquin][NTf2] and 2.64 mS cm-1 and 4.98%, respectively for [C4mquin][I] at its optimum concentration. As to emphasis the role of novel quinolinium based IL containing electrolytes in DSSCs, the efficiency of these cells were compared with DSSCs assembled with a commercialized a used imidazolium IL, [C6mim][I] which recorded a maximum ionic conductivity of 2.23 mS cm-1 with PCE of 5.30%. The developed polymer electrolyte samples were also characterized with X-ray diffractometer (XRD), Fourier transform infrared spectroscopy (FTIR) and Thermogravitimetry Analyzer (TGA). As an additional diagnosis to understand the performance and electrochemical properties of PEs in DSSCs, electrochemical impedance studies were conducted to elucidate charge transfer processes occurring at interfacial within the cell. The performance of the quinolinium containing DSSCs has been improved by enhanced electron transport properties, reduced charge recombination and increased electron lifetime. Overall, the quinolinium based PEs prepared have performed better than anticipated, considering the sole participation with a single salt system, the bulkiness of cation present and quasi-solid nature unlike most commercially available ILs.